Seed Germination Rate and Associated Characters in Rice - Krishnasamy, V.; Seshu, D.V. (Wiley, 1989)
Rapid seed germination will facilitate quick plant stand establishment in direct sown rice (Oryza sativa L.) culture. Sixty‐eight rice cultivars were grown in the field and in the phytotron, and the harvested seed evaluated for germination rate. Cultivars ‘Laxmi’, TNAU(AD)103, IR25924‐92‐1‐3, ‘IR50’, PND160‐2‐1, RNR1429, IR31779‐19‐3‐3‐2‐2, and B3981c‐Pn‐165‐2‐l produced seeds in the field and the phytotron that exhibited superior performance. Therefore, these could be useful donor parents for promoting rapid seed germination when breeding rice for direct‐sown culture. One hundred seed weight was negatively correlated with germination rate. Path analysis suggested that 100 seed weight acted through a high indirect effect of free amino acid content on germination rate. Oxygen uptake and dehydrogenase activity also contributed to germination rate variability. Cultivar differences were evident for germination rate following aging and under low temperature (20 and 15 °C) and moisture stress (−5̄ polyethylene glycol 8000). Hulls did not contribute to variability in germination rate.